CompTIA security+ exam guide, (Exam SY0-601) - Conklin, Wm. Arthur (William Arthur); White, Gregory B. (All-in-one certification series., 2023)
This fully updated study guide covers every topic on the current version of the CompTIA Security+ exam Get complete coverage of all objectives included on the CompTIA Security+ exam SY0-601 from this comprehensive resource. Written by a team of leading information security experts, this authoritative guide fully addresses the skills required to perform essential security functions and to secure hardware, systems, and software. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations. Designed to help you pass the exam with ease, this definitive volume also serves as an essential on-the-job reference. Covers all exam domains, including: threats, attacks, and vulnerabilities; architecture and design; implementation; operations and incident response; and governance, risk, and compliance. Online content includes: 250 practice exam questions and a test engine that provides full-length practice exams and customizable quizzes by chapter or by exam domain.